Microstructural characteristics and physical properties of corn-based extrudates affected by the addition of millet, sorghum, quinoa and canary seed flour - Rolandelli, Guido; García Navarro, Yoja Teresa; García Pinilla, Santiago; Farroni, Abel Eduardo; Gutiérrez López, Gustavo Fidel; Buera, María del Pilar (Elsevier, 2020)
Corn flour blends including 25 % of pearl millet, red sorghum, quinoa or canary seed flours, not deeply studied in the extrusion process of corn-based products, were used for extrudates production. Several physical, mechanical and microstructural properties, as well as water adsorption behavior were analyzed and compared to 100 % corn flour systems. The use of these flours increased the protein and fiber contents and modified several characteristics of the extrudates. The addition of quinoa and canary seed flour enhanced the expansion ratio and water absorption indexes, which could be attributed to their high protein and fiber contents. All extruded blends were darker than the control, with lower L* and higher a* values. A relationship between the microstructural characteristics, crystallinity and several physical properties was found, related to blends composition. The addition of flours with high crude fiber levels reduced hardness values and increased crystallinity of the products. The application of novel ingredients for human consumption is promissory for their re-valorization and further resource exploitation.